Depressive symptoms and activity in a sample of nursing home residents - Diegelmann, Mona (2018)
Objectives. The present dissertation focused on nursing home (NH) residents’ depressive symptoms and the role of social activity, functional ability, and physical activity training in explaining these symptoms. First, the interplay of residents’ basic competence (BaCo), expanded everyday competence (ExCo), and depressive symptoms was considered (Study I). The mediating role of perceived control was also examined. Building on the importance of BaCo for residents’ depressive symptoms, the effect of a BaCo-enhancing physical activity program (LTCMo) on residents’ depressive symptoms development was investigated (Study II). Furthermore, to better understand the roles of BaCo and ExCo in residents’ depressive symptoms, ExCo-related activities were differentiated into contact with co-residents and staff, and participation in organized activities. Their respective enjoyabilities were also considered longitudinally (Study III). Finally, the role of depressive symptoms in predicting residents’ sensor-based life-space was explored (Study IV). Design. Data were drawn from the study Long-Term Care in Motion (LTCMo; Current Controlled Trials ISRCTN96090441), which was part of EU’s Social Innovations Promoting Active and Healthy Aging funding scheme [HEALTH.2012.3.2-3]. LTCMo installed a physical activity training in two NHs in Heidelberg. The intervention aimed at promoting both residents’ physical activity behavior and healthy aging at large. It offered multiple training components (BaCo-related group training and optionally serious games training, or individual training) and allowed residents to choose in which components they wished to participate. After the study intervention, the training was handed over to activity coordinators in the NHs, who implemented the training sustainably. Residents were followed for three (NH 1) and four (NH 2) measurement occasions each three months apart (waiting control group in NH 2). At each measurement occasion, new residents were allowed to enter the study. The presented studies were either based on cross-sectional (Studies I and IV) or on longitudinal data, which included the examination of the LTCMo training effect on residents’ depressive symptoms (Studies II and III). Participants. All permanent, non-palliative residents in the homes were approached and those who (or whose legal representative) gave written informed consent, participated. The number of participants considered in the various papers differed depending on the outcome and the study design. For the cross-sectional studies only referring to residents’ first measurements (Studies I and IV), the number of participants ranged between 65 and 196, with fewer residents particularly for the sensor-based life-space assessment in Study IV. In the longitudinal studies (Studies II and III), a maximum of 163 residents with 434 measurement points was considered. At pretest, 41% of the sample resided in NH 1 and 16% lived on dementia-care units; 70% were female. On average, residents were 84 years old (range 53–100), showed moderate cognitive impairment (M[Mini-Mental State Examination] = 20; range = 0–30), and depressive symptoms below the cut-off for clinical relevance (M[GDS-12R] = 3; range = 0–11). Across study time, 17% of pretest participants dropped out, 86% of which were death-related drop-outs. Methods. Measurements used in the present dissertation include resident interviews (e.g., depressive symptoms, activity enjoyability, cognitive performance), functional performance tests (e.g., BaCo-related gait speed), proxy ratings (e.g., ExCo-related activities), information from the obligatory care documentation in the NHs (e.g., demographic data), and sensor-based indoor tracking of residents (life-space). Depressive symptoms as measured with the Geriatric Depression Scale–Residential (GDS-12R) were the main outcome for Studies I to III. While they were modeled as latent variables using item response theory in Study I, they were modeled as gammadistributed scale scores in Studies II and III. Study IV considered several life-space dimensions as outcomes, namely the time away from the resident’s room and the number of life-space zone changes (transits). For the cross-sectional studies, structural equation models (Study I) and linear regressions (Study IV) with full information maximum likelihood estimations were used. For the longitudinal studies, generalized linear mixed models were used. Results. Less BaCo impairment and more ExCo-related activities were found to predict fewer depressive symptoms cross-sectionally (Study I). The paths between the latent factors were robust when cognitive impairment, home affiliation, sex, and age were controlled for. Perceived control mediated the effect of BaCo, but not ExCo, on residents’ depressive symptoms. Focusing on the effect of LTCMo’s BaCo-enhancing training program showed that residents not participating in the intervention experienced steadily increasing depressive symptomatology across study time, while residents receiving the training maintained their pretest level of depressive symptoms throughout (Study II). The training group suffered from significantly fewer depressive symptoms than the non-training group both at posttest and at follow-up. The effect was robust when controlling for home affiliation, sex, age, living on dementia-care unit, and perceived internal and external control which were significant predictors in Study I. When ExCo-related activities were investigated differentially as longitudinally-framed predictors of depressive symptoms (Study III), activity-specific patterns emerged. For self-initiated co-resident contact, the interaction of contact frequency and enjoyability predicted fewer depressive symptoms with fewest symptoms for those residents who frequently had enjoyable co-resident contact. For self-initiated staff contact, however, only marginal main effects of frequency and enjoyability emerged. And for participation in organized in-home activities, participation enjoyability rather than frequency predicted fewer depressive symptoms (Study III). Conforming to Study II, the training effects emerged and were robust to controlling ExCo-related activity frequency, enjoyability, and additional covariates (Study III). Finally, regarding life-space, residents with more depressive symptoms spent significantly less time away from their own room compared to residents with fewer depressive symptoms (Study IV). Depressive symptoms did not, however, affect the number of life-space transits. Conclusions. Findings support that BaCo impairment and ExCo-related activities, their respective enjoyabilities, and physical activity-enhancing training all are important for NH residents’ depressive symptoms. Given sufficient replication, these insights may guide future intervention research and, in the long run, help to create more effective interventions for maintaining low levels of depressive symptoms in NH residents. Beyond the present findings, future research may investigate the potential of combining enjoyable co-resident contact and a physical activity-enhancing training to reduce or maintain the level of residents’ depressive symptoms. Future research may also focus on assumed underlying processes to better identify residents at risk of developing depressive symptoms. As emerging in the present studies, perceived control may be a promising candidate process variable to consider.